A Case Study On Successful Management of Complicated Fistula in Ano with CKD and Septic Shock Through Integrated Surgical Approach: Pharmaceutical Science-Pharma - Soni, Dr. Shreya; Asutkar, Dr. Sheetal; Kumar Upadhyay, Dr. Sandeep; Yadav, Dr. Yogesh (International Journal of Life Science and Pharma Research, 2023)
Swelling, discomfort, redness, soreness, and a localized increase in temperature are the clinical signs of an abscess. Fistula in ano,the complication most frequently with perianal abscess, is caused by poor pus drainage or incorrect dressing in the post-operative stage.Modern science describes treatment as a two-step process, including an incision and drainage. An abscess can be correlated to Vidradhi inAyurveda. The irritated Dosha affects the tweak, rakta, means, media, and asthi; majja becomes localized and causes a problematic swelling knownas Vidradhi that is deeply ingrained, painful, and expands steadily. When its Pakwa avastha is complete, the vidradhi opens up or bursts. At thisstage, we must perform bhedhana karma to drain the vitiated materials that cause a cavity. The case presented was a recurrent Perianalabscess associated with fistula in ano with Chronic Kidney Disease (CKD) in which the patient had severely deranged Kidney functions, poorsigns of oral nutrition, swollen feet and ankles, puffiness around eyes, oliguria leading to Septic Shock, was managed through Surgical andintegrated approach of Ayurveda. The method followed here is pre-operative medications which was the utmost emergency as the patientwas in Septic shock, and then the surgical management, i.e., Incision (Bhedana) leading to immediate drainage of peri-anal abscess followed byKsheerasutra application for complete drainage along with cutting & healing of the cavity. The planned treatment of the Ksheerasutra applicationafter I & D resulted in a complete cure for the condition. This case study provides the successful emergency management of Gudagata vidradhiwith Bhagandara and comorbidities via surgical & Ayurvedic management.